Seafood, nutrition and human health: A synopsis of the nutritional benefits of consuming seafood - McManus, Alexandra; Newton, Wendy (Centre of Excellence Science, Seafood and Health, Curtin Health Innovation Research Institute, Curtin University, 2011)
Seafood as a whole food is highly nutritious. Benefits to human health associated with the consumption of seafood are noted for multiple bodily organs and physiological functions. Seafood compares favourably with other protein sources as it offers superior macronutrients in the ideal form of lean proteins combined with healthy omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFAs),and a wide array of highly bioavailable micronutrients.This exposition investigates the role of key nutrients present in seafood on human health. Particular focus is placed on marine sourced omega 3 fatty acids, protein, vitamins A, B12, D and E, iodine, selenium, calcium, zinc and iron.